2021
DOI: 10.1159/000519046
|View full text |Cite
|
Sign up to set email alerts
|

Necessity of Intraoperative Level IIA Lymph Node Dissection in Patients with Carotid Body Tumors: A Retrospective Study of 126 Cases

Abstract: <b><i>Background:</i></b> Carotid body tumors (CBTs) are relatively uncommon neoplasms that rarely have malignant potential. However, malignant CBTs (MCBTs) are still associated with a poor prognosis and the treatment is still challenging clinically. Therefore, we evaluated the necessity of intraoperative level IIA lymph node dissection in patients with CBT. <b><i>Methods:</i></b> The clinical characteristics, intraoperative details, and pathological diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Some suggest that concomitant lymph node dissection does not appear to add value in the absence of clinical suspicion for malignancy, yet a recent study showed that intraoperative dissection of level IIA lymph nodes in CBT patients might contribute to the diagnosis and prognosis of MCBTs. [24,25] Distant spread was rare in our reported cases. When the primary tumor and locoregional lymph nodes were excised, neither further regional lymph node metastasis nor distant spread was observed during long-term follow-up in most cases.…”
Section: Discussionmentioning
confidence: 67%
“…Some suggest that concomitant lymph node dissection does not appear to add value in the absence of clinical suspicion for malignancy, yet a recent study showed that intraoperative dissection of level IIA lymph nodes in CBT patients might contribute to the diagnosis and prognosis of MCBTs. [24,25] Distant spread was rare in our reported cases. When the primary tumor and locoregional lymph nodes were excised, neither further regional lymph node metastasis nor distant spread was observed during long-term follow-up in most cases.…”
Section: Discussionmentioning
confidence: 67%
“…Finally, 132 papers were considered appropriate for the present SR, for a total of 337 patients (Figure 1). Among these articles, 20 (158 patients) included 5 or more patients (Table 1) 18–39 and were considered for the proportion MA. The remaining 112 studies (179 patients), represented by case reports or case series with <5 patients, are reported in Table S1 3,40–152 …”
Section: Resultsmentioning
confidence: 99%
“…Overall, 158 patients with MCBTs were included in the MA from the 20 case series with five or more patients 18–39 . The diagnosis of MCBT in these surgical series was a rare occurrence, with a pooled proportion of 7.3% (95% CI: 5.8%–8.9%; I 2 = 33%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations